2018
DOI: 10.1186/s12870-018-1517-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genomic loci associated with 21chlorophyll fluorescence phenotypes by genome-wide association analysis in soybean

Abstract: BackgroundPhotosynthesis is able to convert solar energy into chemical energy in the form of biomass, but the efficiency of photosynthetic solar energy conversion is low. Chlorophyll fluorescence measurements are rapid, non-destructive, and can provide a wealth of information about the efficiencies of the photosynthetic light reaction processes. Efforts aimed at assessing genetic variation and/or mapping of genetic loci associated with chlorophyll fluorescence phenotypes have been rather limited.ResultsEvaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 93 publications
1
14
0
Order By: Relevance
“…Subsequently, we observed a low (< 0.5) heritability value for NPQ relaxation parameters in the NAM population using current screening approaches in a field environment. This is similar to heritability estimates from OJIP measurements of chlorophyll fluorescence in a larger panel of soybean genotypes (Herritt et al, 2018), and those reported for other photosynthetic traits such as Jmax in wheat (0.32; (Driever et al, 2014)).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Subsequently, we observed a low (< 0.5) heritability value for NPQ relaxation parameters in the NAM population using current screening approaches in a field environment. This is similar to heritability estimates from OJIP measurements of chlorophyll fluorescence in a larger panel of soybean genotypes (Herritt et al, 2018), and those reported for other photosynthetic traits such as Jmax in wheat (0.32; (Driever et al, 2014)).…”
Section: Discussionsupporting
confidence: 86%
“…Chlorophyll fluorescence was evaluated in two studies with field grown soybean, using canopy reflectance to calculate photochemical reflectance index (PRI), which is a proxy for NPQ (Herritt et al, 2016), and OJIP transients to look at variation in fluorescence kinetics (Herritt et al, 2018).…”
Section: Symbol Description Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when starting any experiment, a set of standard A-Ci curves should be performed to test that the method is working for each species and/or environmental condition. Therefore, this RACiR methodology only appears to be worth the effort when analyzing hundreds of samples at the same environmental condition as is often the case for GWAS and/or QTL experiments ( Dhanapal et al, 2015 ; Herritt et al, 2018 ; Luo et al, 2018 ). For small experiments where only a few cultivars/species are to be analyzed, it is more reasonable to do standard A-Ci curve measurements even if it is more time consuming, as they can be used to obtain other important information such as C c , g m ( Harley et al, 1992 ), R d and Γ that can give further valuable information about the physiological state of the plant.…”
Section: Semi- and High-throughput Phenotyping Techniques To Measure mentioning
confidence: 99%
“…Some studies have been conducted to discover QTLs associated with Chl fluorescence traits under various conditions, such as normal (Zhang et al 2010), heat stress (Azam et al 2015, Bhusal et al 2018, and waterlogging (Bertholdsson et al 2015) in wheat and barley. Herritt et al (2018) identified several genomic loci associated with JIP-test parameters through genome-wide association study in soybean. However, till date no attempt has been made to identify QTLs associated with Chl fluorescence parameters under salt stress in rice.…”
Section: Introductionmentioning
confidence: 99%